2019
DOI: 10.3390/jcm8060762
|View full text |Cite
|
Sign up to set email alerts
|

Disorder of Coagulation-Fibrinolysis System: An Emerging Toxicity of Anti-PD-1/PD-L1 Monoclonal Antibodies

Abstract: A disruption of immune checkpoints leads to imbalances in immune homeostasis, resulting in immune-related adverse events. Recent case studies have suggested the association between immune checkpoint inhibitors (ICIs) and the disorders of the coagulation-fibrinolysis system, implying that systemic immune activation may impact a balance between clotting and bleeding. However, little is known about the association of coagulation-fibrinolysis system disorder with the efficacy of ICIs. We retrospectively evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 77 publications
(199 reference statements)
0
43
0
Order By: Relevance
“…Production of inflammatory cytokines subsequently suppresses the antithrombotic response of endothelial cells and promotes procoagulant activity. 34 Recent studies have suggested that aberrant activation of the innate immune response is associated with thrombosis and atherothrombosis. 35 Additionally, several studies have investigated the role of PD-1 and its impact on atherogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Production of inflammatory cytokines subsequently suppresses the antithrombotic response of endothelial cells and promotes procoagulant activity. 34 Recent studies have suggested that aberrant activation of the innate immune response is associated with thrombosis and atherothrombosis. 35 Additionally, several studies have investigated the role of PD-1 and its impact on atherogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…F2, which encodes the coagulation factor II (also known as thrombin), is a pro-inflammatory and pro-coagulant molecule that is elevated in various cancers, including breast and gastric cancers [46,47]. Recent studies showed that disorders of the coagulation-fibrinolysis system are associated with the efficacy of immune-checkpoint inhibitors [48]. Thrombin activates platelets in the tumor Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Mice lacking PD-L1 are susceptible to autoimmune diseases, suggesting the importance of PD-L1 in maintaining immune tolerance [ 51 ]. In vitro work showed that PD-L1 is expressed by APCs, in a steady-state condition, and serve as a self-regulatory mechanism to maintain haemostasis and suppress T cell activation [ 52 ].…”
Section: Discussionmentioning
confidence: 99%